2015
DOI: 10.4238/2015.june.29.17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of UGT1A1 and ERCC1 gene polymorphisms with the outcome of combined irinotecan plus cisplatin treatment in recurrent ovarian cancer

Abstract: ABSTRACT. The aim of this study was to define the genotypes of UGT1A1 and ERCC1 and to examine their relationship with the efficacy and toxicity of a combination therapy of irinotecan and cisplatin in patients with advanced ovarian cancer. The allelic frequencies of the UGT1A1 and ERCC1 variants in a group of 89 patients with advanced ovarian cancer were determined. The relationship between the adverse events of irinotecan-based chemotherapy and the efficacy of cisplatin in patients with advanced ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…В схемах химиотерапии рака толстой кишки (распространенного рака желудка, рака яичников, рака легких и других) наиболее часто используются препараты на основе фторпиримидинов (5-фторурацил и капецитабин), а также иринотекан [3][4][5][6]. Дефицит фермента дигидропиримидин дегидрогеназы (DPYD), наследуемый по аутосомнорецессивному типу, является основной причиной тяжелой и даже летальной токсичности лекарственных препаратов на основе 5-фторурацила (5-ФУ).…”
Section: Introductionunclassified
“…В схемах химиотерапии рака толстой кишки (распространенного рака желудка, рака яичников, рака легких и других) наиболее часто используются препараты на основе фторпиримидинов (5-фторурацил и капецитабин), а также иринотекан [3][4][5][6]. Дефицит фермента дигидропиримидин дегидрогеназы (DPYD), наследуемый по аутосомнорецессивному типу, является основной причиной тяжелой и даже летальной токсичности лекарственных препаратов на основе 5-фторурацила (5-ФУ).…”
Section: Introductionunclassified
“…Among these studies, 16 studies investigated the associations in Caucasians 11-15, 18, 25-35, 40 in Asians 3, 9, 16, 17, 36-62, and two in mixed population or not reported 63, 64. All studies were retrospective or prospective studies, including 29 metastatic colorectal cancer (mCRC) studies, five metastatic non-small cell lung cancer (mNSCLC), three advanced gastric cancer (GC) studies, two SCLC studies, and two advanced esophageal cancer studies and others.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods such as surgery, radiotherapy, and chemotherapy are widely applied for the clinical treatment of cancer. Irinotecan-based chemotherapy is one of the most used chemotherapies for patients with advanced gastric cancer, ovarian cancer, metastatic colorectal cancer, and other cancers 3-5. Irinotecan, a camptothecin derivative, is mainly transported into liver by solute carriers and metabolized into ametabolite, SN-38, by a carboxylesterase 6.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the T allele may also be more sensitive to PDs [31,32]. Globally, many studies in non-small cell lung cancer [8], ovarian cancer [9], gastric cancer [10], esophageal cancer [11], pancreatic cancer [12], and colorectal cancer [13] have shown patients with the CT or TT genotypes in ERCC1 C118T mutation to be more sensitive to PDs when compared to patients with the CC genotype.…”
Section: Discussionmentioning
confidence: 99%
“…ERCC1 single nucleotide polymorphisms (SNPs), particularly the C-T mutation at the 118 th codon in exon 4, can affect gene expression level and change gene copy number, thus affecting the resistance to PDs [8]. Many studies have reported that the ERCC1 C118T mutation exhibits a predictive value for PD efficacy and disease prognosis in different types of cancers, such as non-small cell lung cancer [8], ovarian cancer [9], gastric cancer [10], esophageal cancer [11], pancreatic cancer [12], and colorectal cancer [13]. Therefore, screening ERCC1 mutation before chemotherapy may have important guiding significance and prognostic value for chemotherapy.…”
Section: Introductionmentioning
confidence: 99%